Evangelicals in Democratic Chile: Clash of Generations? - Fediakova, E (2014)
Historically, the Chilean evangelical Churches belonged to a marginal religious category, discriminated against by the dominant Catholic culture. Nevertheless, during the last 20 years, new generations of believers are challenging the authorities and traditional power relations in their Churches, elaborating new forms of civil participation and changing the previous evangelical identity. The higher levels of education and living standards allow the religious youth to question their pastors power and to form more secular relations with national politics and society. This could be leading to a clash between the new generations of evangelicals with a university education and the established Church authorities, producing more diversity within evangelical religiosity, conflicts inside the communities, and/or extra-ecclesial forms of the religious manifestations: inter-denominational movements, research centers, non-governmental organizations, websites. From another perspective, higher education and relative secularization are helping to liberate young evangelicals from marginality and include them in society, with the same socio-political status as Catholic and agnostic Chileans. © The Author(s) 2013.